Moonbeams from the Larger Lunacy - Leacock, Stephen, 1869-1944 (Salt Lake City, UT : Project Gutenberg, 2003)
"Moonbeams from the Larger Lunacy" by Stephen Leacock is a collection of satirical short stories written during the early 20th century. The text addresses various subjects, including absurdities of society, modern literature, and the human condition, often with a humorous twist. Through whimsical narratives and clever observations, Leacock critiques contemporary events and explores the follies of people, making the collection both entertaining and thought-provoking. The beginning of the book opens with a preface where Leacock humorously discusses the process of turning magazine articles into a book. This sets the stage for the first chapter titled "Spoof," which introduces the character Lancy de Vere, a young Englishman traveling to America under an assumed name. Onboard the ship, de Vere becomes entranced by a mysterious girl he sits next to, and as they engage in a conversation about America, his fascination with her grows. Their dialogue blends fascination for the land with humorous misunderstandings, hinting at deeper themes of identity and societal expectations that will unfold throughout the narrative. (This is an automatically generated summary.)
Spoof: a thousand guinea novel -- The reading public -- Afternoon adventures at my club -- Ram Spudd -- Aristocratic anecdotes -- Education made agreeable -- An every-day experience -- Truthful oratory -- Our literary bureau -- Speeding up business -- Who is also who -- Passionate paragraphs -- Weejee the pet dog -- Sidelights on the supermen -- The survival of the fittest -- The first newspaper -- In the good time after the war.
Release date is 2003-05-01
Gardner Buchanan with help from the distributed proofers system created by Charles Franks
Keywords: Canadian wit and humor